Combinatorial Therapy of Letrozole- and Quercetin-Loaded Spanlastics for Enhanced Cytotoxicity against MCF-7 Breast Cancer Cells - Aml I. Mekkawy; Nermin E. Eleraky; Ghareb M. Soliman; Mohamed G. Elnaggar; Marwa G. Elnaggar (Pharmaceutics, 2022)
Breast cancer is the most widespread cancer in women with rising incidence, prevalence, and mortality in developed regions. Most breast cancers (80%) are estrogen receptor–positive, indicating that disease progression could be controlled by estrogen inhibition in the breast tissue. However, drug resistance limits the benefits of this approach. Combinatorial treatment could overcome the resistance and improve the outcome of breast cancer treatment. In the current study, we prepared letrozole-(LTZSPs) and quercetin-loaded spanlastics (QuSPs) using different edge activators—Tween 80, Brij 35, and Cremophor RH40—with different concentrations. The spanlastics were evaluated for their average particles size, surface charge, and percent encapsulation efficiency. The optimized formulations were further examined using transmission electron microscopy, Fourier transform infrared spectroscopy, in vitro drug release and ex vivo skin permeation studies. The prepared spherical LTZSPs and QuSPs had average particle sizes ranged between 129–310 nm and 240–560 nm, respectively, with negative surface charge and high LTZ and Qu encapsulation (94.3–97.2% and 97.9–99.6%, respectively). The in vitro release study of LTZ and Qu from the selected formulations showed a sustained drug release for 24 h with reasonable flux and permeation through the rat skin. Further, we evaluated the in vitro cytotoxicity, cell cycle analysis, and intracellular reactive oxygen species (ROS) of the combination therapy of letrozole and quercetin either in soluble form or loaded in spanlastics against MCF-7 breast cancer cells. The LTZSPs and QuSPs combination was superior to the individual treatments and the soluble free drugs in terms of in vitro cytotoxicity, cell cycle analysis, and ROS studies. These results confirm the potential of LTZSPs and QuSPs combination for transdermal delivery of drugs for enhanced breast cancer management.